Phytochemical Analysis of Bulung Boni (Caulerpa cylindracea S.) N- Hexane Extract with Gc-Ms Method and Toxicity Test on Mice (Mus musculus L.) - Silalahi, May Disa Br; Wirawan, I Gede Putu; Wijaya, I Nyoman; Suada, I Ketut; Phabiola, Trisna Agung; Astaykina, Angelika (International Journal of Biosciences and Biotechnology; Vol 10 No 2 (2023): INTERNATIONAL JOURNAL OF BIOSCIENCES AND BIOTECHNOLOGYDO - 10.24843/IJBB.2023.v10.i02.p06, 2023)
One of the marine resource commodities owned by Indonesia is seaweed. Bulung boni is one type of seaweed that grown in Indonesia. Bulung boni is the regional name of Caulerpa cylindracea . Bulung boni is usually used as a food and medicine for most people in Bali. The purpose of this research is to study the content of phytochemical compounds in n-hexane extract of bulung boni and determine the toxicity effect on mice ( Mus musculus ). The methods used in this study were maceration, GC-MS (Gas Chromatography-Mass Spectrometry), observation, and calculation with the Thomson and Weil formula. This study used 24 mice as experimental animals. Mice were divided into 6 treatment groups, group 1 as control was given 1% Na-CMC solution, groups 2-6 were given test extracts with doses, 100, 200, 300, 400, 500 mg/30 g BW mice. The results showed the highest compound contained in the n-hexane extract of bulung boni was Hexadecanoic acid, methyl ester with an AUC value of 35.21%. Toxicity tests on mice showed no deaths experienced by mice, so the LD 50 value determined was pseudo at 16.6 g/ kg BW and fell into the practically non-toxic category